2015
DOI: 10.1017/jrr.2015.3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship-Focused Coping Patterns of Japanese Child-Rearing Couples

Abstract: This study elucidated the relationship-focused coping patterns of Japanese child-rearing couples. Participants were 101 Japanese couples with at least one pre-school child who was attending one of four daycare centres. Questionnaires included a Japanese version of the relationship-focused coping questionnaire, the Kansas Marital Satisfaction Scale, and the WHO-5 Well-Being Index. Cluster analysis revealed three relationship-focused coping patterns: ‘wife escapes/husband combines’, ‘mutual active relationship m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Only one study has examined the role of protective buffering in couples in a non-medical context. This study examined Japanese couples with pre-school children (Kurosawa et al, 2015) and found no significant associations of protective buffering with either relationship satisfaction or well-being, suggesting the possibility that protective buffering may play a different role when coping with non-medical stressors. However, the same study found that couples with more serious stressors tended to use protective buffering as a coping strategy more often.…”
Section: Individual Negative Dc: Protective Buffering (Rfm)mentioning
confidence: 83%
See 1 more Smart Citation
“…Only one study has examined the role of protective buffering in couples in a non-medical context. This study examined Japanese couples with pre-school children (Kurosawa et al, 2015) and found no significant associations of protective buffering with either relationship satisfaction or well-being, suggesting the possibility that protective buffering may play a different role when coping with non-medical stressors. However, the same study found that couples with more serious stressors tended to use protective buffering as a coping strategy more often.…”
Section: Individual Negative Dc: Protective Buffering (Rfm)mentioning
confidence: 83%
“…Only one study has examined active engagements as a DC strategy for couples to manage stress in general. In that study Kurosawa et al (2015) found that in Japanese couples with pre-school children active engagement was linked with higher relationship satisfaction.…”
Section: Individual Positive Dc: Active Engagement (Rfm)mentioning
confidence: 95%
“…The Japanese version of the Kansas Marital Satisfaction Scale (KMS; Schumm et al., ) was used to measure perceived marital satisfaction (Kurosawa et al., ). The KMS consists of three items: “How satisfied are you with your marriage?” “How satisfied are you with your husband/wife as a spouse?” and “How satisfied are you with your relationship with your husband/wife?” The scale uses a seven‐point Likert scale (1 = extremely dissatisfied to 7 = extremely satisfied), resulting in scores ranging from 3 to 21.…”
Section: Methodsmentioning
confidence: 99%
“…The Japanese version of the Kansas Marital Satisfaction Scale (KMS; Schumm et al, 1986) was used to measure perceived marital satisfaction (Kurosawa et al, 2015). The KMS consists of three items: "How satisfied are you with your marriage?"…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation